Psychological Safety, Job Crafting, and Employability: A Comparison Between Permanent and Temporary Workers - Plomp, Judith; Tims, Maria; Khapova, Svetlana N.; Jansen, Paul G. W.; Bakker, Arnold B. (Frontiers in Psychology, 2019)
Employability is one of the leading challenges of the contemporary organizational environment. While much is known about the positive effects of job crafting on employees’ employability in general, little is known about its effects when employment contacts are different. Differentiating between temporary and permanent workers, in this paper we investigate how in the environment of psychological safety, these two types of employees engage in job crafting and how job crafting is related to their perceived employability. Data were collected among two samples, consisting of temporary agency workers (N = 527) and permanent employees (N = 796). Structural equation modeling analyses indicated a different pattern of results for the two groups: for permanent employees, increasing challenging job demands was positively, and decreasing hindering job demands was negatively related to perceived employability. Moreover, psychological safety was related to all job crafting dimensions. For agency workers, only increasing structural job resources was related to employability, while psychological safety was negatively associated with crafting hindrances. These findings suggest that a climate of psychological safety is particularly effective for permanent employees in fostering job crafting and employability.